Penerapan Zahir Accounting Dalam Transaksi Pembelian Barang PD. Mitrasarana Komputindo Pontianak - Latifah Latifah; Prianka Larasati (Jurnal Sistem Informasi Akuntansi, 2020)
Manually accounting processing has more risks compared using a computerized system. For example, in the simplest terms of journal entry, there is often a doubling, or twice the input with the same memorandum number in different transactions. This make an imbalance of ledgers and financial reports that are made later, this is what happens to PD. Mitrasarana Komputindo which still uses the manual system in preparing its financial statements. Most of the data recording is using Microsoft Excel, from customer and vendor data, account data, general journals till financial reports. This can have an impact on financial statements ineffective and requires a long time because all data is not directly related. The occurrence of errors can also result in inaccuracies in the financial statements produced and delays in finding the data needed. PD Mitrasarana Komputindo requires an accounting application can make it easy to process financial data and business decisions quickly and accurately. Then it can reduce errors that can occur in processing financial data and if we want to find the data it will be easier and faster than recording data in writing. Using Zahir Accounting 5.1 version be an alternative in processing existing data, and expected to reduce errors, both in the input and calculation process.